Cortical Bone Trajectory Pedicle Screw Fixation in Surgical Treatment of Monosegmental Pyogenic Lumbar Spondylodiskitis - Shin, Jae-Hyuk; Kim, Sang-II; Jung, Jiyoung; Rhyu, Kee-Won (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Object Pedicle screw fixation has been widely used in surgical treatment for infective lumbar spondylodiskitis to prevent instability and deformity. The cortical bone trajectory pedicle screw (CBTPS) fixation is a minimally invasive posterior spinal fixation system that runs from the pedicle's entry point of the caudiomedial region toward the cephalad-divergent direction. Successful results with CBTPS fixation have been reported to treat degenerative and osteoporotic spinal diseases. This study aims to investigate the clinical feasibility of CBTPS in the surgical treatment of pyogenic lumbar spondylodiskitis.Patient and Methods We retrospectively retrieved 20 consecutive patients from two academic centers who were surgically treated for monosegmental lumbar pyogenic spondylodiskitis. The primary surgical treatment was the anterior lumbar interbody fusion with decompression, debridement, and reconstruction using an autogenous iliac strut bone graft. One to 2 weeks after the primary surgery, patients underwent a second surgery for posterior instrumentation using conventional pedicle screws (CPS; group I) and CBTPS (group II). Radiographic parameters of the deformity angle at the fusion segment and clinical parameter of visual analog scale (VAS) scores were assessed preoperatively, postoperatively, and at the last follow-up.Results There were 10 patients in each group. The mean follow-up periods of groups I and II were 51.10 ± 6.95 and 28.60 ± 9.31 months, respectively. Intergroup analysis indicated the two groups area age-matched (p = 0.38), but initial C-reactive protein (CRP; mg/dL, p = 0.04), CRP normalization (months, p = 0.00), and follow-up duration (months, p = 0.00) were heterogeneous. Meanwhile, deformity angles (segmental lordosis) between the two groups were not significantly different preoperatively (p = 0.25), postoperatively (p = 0.13), and at last follow-up (p = 0.38). The intragroup analysis indicated a significant postoperative increase of lordosis in both group I and II (p = 0.00 and 0.04, respectively) with subsequent subsidence. Lordosis remained increased at the last follow-up with or without significance (group I, p = 0.02; group II, p = 0.62). Both groups showed significant improvement in VAS scores (group I, p = 0.00; group II, p = 0.00).Conclusion In monosegmental lumbar spondylodiskitis, posterior stabilization of the anterior strut bone graft by CBTPS and CPS was comparable via the radiographic parameter of segmental lordosis or deformity angle. Our observation suggests the clinical feasibility of CBTPS in the treatment of relatively mild monosegmental pyogenic lumbar spondylodiskitis.
Keywords: monosegmental lumbar pyogenic spondylodiskitis; surgical treatment; cortical bone trajectory pedicle screw